One-year quality of life and functional outcomes of transoral robotic surgery for carcinoma of unknown primary - YUMUŞAKHUYLU, ALİ CEMAL (WILEY, 2017)
Background: The purpose of this study was to assess the quality of life (QOL) outcomes in patients who underwent transoral robotic surgery (TORS) for carcinoma of unknown primary (CUP). Methods: Twenty-nine patients with CUP were administered the Head and Neck Cancer Inventory (HNCI) prospectively to evaluate QOL preoperatively and postoperatively. Results: There was statistically and clinically significant deterioration in 2 of 4 domains (eating and social disruption) in the immediate aftermath of TORS. There was statistically and clinically meaningful deterioration in all 4 domains at 3 months relative to baseline, and there remained statistically and clinically meaningful deterioration in 2 of 4 domains at 6 months compared to baseline. These 2 domains remained statistically and clinically worse than baseline at 12 months. Speech and aesthetics domain scores were comparable at baseline and 12 months. Conclusion: Patients reported difficulties with eating and social disruption over the course of 1 year, but problems with speech and appearance abated.
Keywords: aesthetics; carcinoma of unknown primary; head and neck cancer; quality of life; transoral robotic surgery; LYMPH-NODE METASTASES; SQUAMOUS-CELL CARCINOMA; OROPHARYNGEAL CARCINOMA; NECK-CANCER; PRIMARY TUMORS; PRIMARY SITE; HEAD; MANAGEMENT; RECONSTRUCTION; CHEMOTHERAPY